Analysing tree–neighbourhood interactions in ecotones of montane evergreen and deciduous forests in China. (8th April 2019) - Wang, Qinggang; Chi, Xiulian; Tang, Zhiyao; Jiang, Mingxi
Abstract: Questions: Do neighbourhood interactions in trees result in discernible spatial and phylogenetic signals among their nearest neighbours in a montane evergreen and deciduous forest? Are neighbourhood patterns of different species associated with their abundances and traits? Location: Badagongshan National Nature Reserve, Hunan, China. Methods: We used four nearest‐neighbour indices: average spatial distance to the nearest conspecific cohort‐mate (SNCC), average spatial distance to the nearest conspecific adult (SNCA), average phylogenetic distance to the nearest heterospecific cohort‐mate (PNHC), and average phylogenetic distance to the nearest heterospecific adult (PNHA). We focused on 77 abundant species in a 25‐ha plot. We evaluated whether the changes in SNCC, PNHC, SNCA and PNHA deviated significantly from expected values of spatially random mortality during two life stage transitions. Results: For more than one‐fourth of the tested species, the changes in SNCC and PNHC deviated significantly from the expectations of random mortality. Nearly one‐third of the tested species showed greater SNCC at the juvenile stage than expected of random mortality, which may be mainly explained by conspecific tree competition for space and resources. Approximately 60% and 40% of the tested species showed significantly smaller SNCA and PNHA than expected by random mortality, respectively, which suggests the effects of facilitation and habitat filtering. In addition, abundant and taller species were suppressed by conspecific cohorts to a greater degree than locally rarer and shorter species. Deciduous species were more negatively influenced by conspecifics and closely related heterospecifics than evergreen species. Conclusions: Our study focused on long‐term responses of individual species to their conspecific and phylogenetic neighbourhoods and revealed the associations between species traits and neighbourhood patterns. Such trait–neighbourhood interactions provide support for stabilizing mechanisms driving species coexistence in this species‐rich subtropical forest. Abstract : Using a null model approach, this study examines conspecific and phylogenetic interactions with nearest neighbours and reveals the associations between species traits and neighbourhood patterns in a montane evergreen and deciduous forest in China. Our study highlights the role of trait–neighbourhood interplays in the local stable coexistence of different species in species‐rich forests.